Management of Equivalent Education Package C Program in Non-Formal Education Unit Sanggar Learning Activity Study Unit of Southeast Minahasa Regency - Samalo, Dodi C.; Sumual, Tinneke E. M.; Monigir, Norma N. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The purpose of this study was to analyze in depth the management of Equivalency Education Package C Program SPNF SKB Minahasa Tenggara Regency, especially regarding the planning, organization, implementation and supervision of the Package C Program at SPNF SKB Minahasa Tenggara Regency. This study uses a qualitative approach, which aims to describe the role of educational units in managing the management of equivalency education at SPNF SKB Minahasa Tenggara Regency. The results of the study prove that the management of Equivalency Education Package C program at SPNF SKB Minahasa Tenggara Regency is implemented through four main stages, namely: 1) Planning. Overall, the planning process has been carried out systematically, participatively, and responsively to the needs of the community. 2) Organizing. Overall, the organization of the Package C Program at SPNF SKB Minahasa Tenggara Regency has been carried out with a systematic, participatory, and needs-based managerial approach. 3) Implementation. Overall, the implementation of the Package C Program at SPNF SKB Minahasa Tenggara Regency has gone quite well and reflects the application of the principles of flexibility, active participation, and adaptation to the needs of students. 4) Supervision and Evaluation. Overall, supervision and evaluation in the Package C Program at SPNF SKB Southeast Minahasa Regency have a very important role in ensuring the quality and sustainability of the program